The development of animation as one of the tourism product in Melaka - Samuri, Azizah; Ismail, Nur Fadhliah (2014)
Tourism is travel for recreational, leisure, or business purposes, usually of a limited duration. Tourism is commonly associated with trans-national travel, but may also refer to travel to another location within the same country. The World Tourism Organization defines tourists as people "traveling to and staying in places outside their usual environment for not more than one consecutive year for leisure, business and other purposes". Tourism is one of the most attractive and the fastest growing industry around the world. According towards World Travel and Tourism Council (WTTC), tourism in 2005 was turned out to be the second largest industry, which accounted for 3.8 per cent of global Gross Domestic Product - GDP (Rosli & Azhar, 2007). This development was promoted by governments in both developed and developing countries. Malaysia is a relatively new entrant into tourism in relation to its ASEAN neighbors’. Serious efforts in developing and promoting tourism began only with the establishment of the Tourist Development Corporation Malaysia (TDCM) in 1972 and it took another 15 years before a specific ministry, the Ministry of Arts, Culture and Tourism (MOCAT) was set up in 1987. In April 2004, MOCAT was split to facilitate the establishment of a separate ministry responsible solely for matters related to tourism i.e. the Ministry of Tourism (MOT).